The effects of waste marble dust applying as a fine sand on the mechanical properties of concrete - Demirel, Bahar (Stowarzyszenie Producentow Cementu, 2010)
In this experimental study, the effects of using waste marble dust (WMD) as a fine material on the mechanical properties of the concrete have been investigated. For this purpose four different series of concrete-mixtures were prepared by replacing the fine sand (passing 0,25 mm sieve) with WMD at proportions of 0%, 25%, 50% and 100% by weight. In order to determine the effect of the WMD on the compressive strength with respect to the curing age, compressive strengths of the samples were recorded at the curing ages of 3, 7, 28 and 90-days. In addition, the porosity values, ultrasonic pulse velocity (UPV), dynamic modulus of elasticity (Edin) and the unit weights of the series were determined. Finally, all of the data were compared with each other. It was observed that the addition of WMD such that would replace the fine material passing through a 0.25 mm sieve at particular proportions has displayed an enhancing effect on compressive strength.
Wp?yw odpadowego py?u marmurowego zastosowanego jako substytut drobnej frakcji piasku na w?a?ciwo?ci mechaniczne betonu
Keywords: Different Curing Conditions; Expanded Perlite Aggregate; Self-Compacting Concrete; Mineral Admixtures; Lightweight Concrete; Performance; Durability; Slag